Mathematics education at Universiti Teknologi Malaysia (UTM) : learning from experience - Mohd. Yusof, Yudariah; Abdul Rahman, Roselainy (Penerbit UTM Press, 2001)
This paper will describe mathematics education in UTM. A review of the problems faced in the learning and teaching of mathematics in the last decade will be discussed. Several academic strategies have been implemented in the past, aimed at overcoming students’ learning difficulties, narrowing the abilities gap among the students, as well as facilitating the transition from secondary to tertiary learning. A summary of these programmes will be presented. There are now changes taking place that will further impact the direction of education in UTM. There is an increase in the number of students intake, a movement towards integrating the use of electronic media in teaching and an expansion of virtual education to ensure a wider access to education. In particular, for mathematics education, these changes will affect the curriculum development, the teaching methods and the assessment of mathematics learning. Thus the scenario in UTM is set – within the existing academic system, the old problems still persist, approaches have been undertaken and discarded, new strategies implemented periodically and there are now new changes and development to be faced. These experiences must be taken into consideration in order to develop guidelines for future mathematics education in UTM.